1999
DOI: 10.1038/sj.ejcn.1600763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary copper intakes on biochemical markers of bone metabolism in healthy adult males

Abstract: Objective: To investigate the effects of changing from a medium (1.6 mg Cuad) to a low (0.7 mg Cuad) or a high (6.0 mgad) Cu intake on biochemical indices of bone turnover in healthy adult males. Design: A longitudinal intervention trial. Setting: The study was conducted at the Institute of Food Research, Norwich, UK. Subjects: Eleven healthy adult males aged 20 ± 59 y were recruited from Norwich Research Park. Intervention: Subjects were given medium (1.6 mgad), low (0.7 mgad) and high (6.0 mgad) intakes of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
3
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 34 publications
3
38
3
3
Order By: Relevance
“…This is in agreement with the ®ndings of several studies which have shown a lack of response of circulating Cp protein levels to daily supplementation with 2 ± 6 mg Cu (Medeiros et al, 1991;Eaton-Evans et al, 1996;Baker et al, 1999b). However, it has been suggested that the speci®c enzymatic activity of Cp, de®ned as the ratio of enzyme activity to the immunoreactive protein, is a better indicator of Cu status than either the enzymatic activity or immunoreactive protein alone (Milne et al, 1988;Milne, 1994).…”
Section: Dietary Cu Supplementation and Bone Biomarkerssupporting
confidence: 87%
See 4 more Smart Citations
“…This is in agreement with the ®ndings of several studies which have shown a lack of response of circulating Cp protein levels to daily supplementation with 2 ± 6 mg Cu (Medeiros et al, 1991;Eaton-Evans et al, 1996;Baker et al, 1999b). However, it has been suggested that the speci®c enzymatic activity of Cp, de®ned as the ratio of enzyme activity to the immunoreactive protein, is a better indicator of Cu status than either the enzymatic activity or immunoreactive protein alone (Milne et al, 1988;Milne, 1994).…”
Section: Dietary Cu Supplementation and Bone Biomarkerssupporting
confidence: 87%
“…The increase in erythrocyte SOD activity in the present study after daily supplementation of the usual diet with 3 or 6 mg Cu for 4 weeks may indicate that the Cu status in the subjects was improved by supplementation. This is in contrast with the ®ndings of other Cu intervention studies, which showed that supplementation of the usual diet with additional Cu (in the range 3 ± 6 mgaday) had no effect on erythrocyte SOD (Medeiros et al, 1991;Eaton-Evans et al, 1996;Baker et al, 1999b). For example, we have recently shown in another double-blind, placebo-controlled crossover trial that Cu supplementation with 3 or 6 mg elemental Cuaday for 6 weeks had no effect on erythrocyte SOD or serum Cp protein concentration in healthy adults (12 males and 12 females, aged 22 ± 46 y; Baker et al, 1999b).…”
Section: Dietary Cu Supplementation and Bone Biomarkersmentioning
confidence: 59%
See 3 more Smart Citations